Applying the Successional Weed Management Model for Revegetating a Yellow Starthistle-Infested Dryland Pasture in the Chihuahuan Desert. (1st December 2011) - Sommers IV Sommers IV, William D. William D.; Howery Howery, Larry D. Larry D.; Pendleton Pendleton, Rosemary L. Rosemary L.; Lee Lee, Richard D. Richard D.; Pendleton Pendleton, Burton K. Burton K.
Abstract : A three-year study was conducted in the Chihuahuan Desert in Southwestern New Mexico to evaluate the effectiveness of revegetating a dryland pasture that was heavily infested with yellow starthistle within the context of the successional weed management model. A prescribed burn treatment of the entire study site (designed disturbance) was followed by single-entry revegetation (controlled colonization) and weed suppression (controlled species performance) treatments. Four native perennial grass species were paired with 4 yellow starthistle suppression treatments. We conclude that an integrated, single-entry approach failed to effectively revegetate yellow starthistle-infested dryland pasture in the Chihuahuan Desert, primarily due to a historic severe drought that occurred soon after grasses were seeded. Different strategies and tactics will be required to manage yellow starthistle in the Southwestern USA than have been previously applied in other areas.